Real-world experience of sorafenib maintenance after allogeneic hematopoietic stem cell transplantation for FLT3-ITD AML reveals high rates of toxicity-related treatment interruption - Morin, Sarah; Giannotti, Federica; Mamez, Anne-Claire; Pradier, Amandine; Masouridi-Levrat, Stavroula; Simonetta, Federico; Chalandon, Yves (Frontiers in Oncology, 2023)
Sorafenib significantly improves survival of FLT3-ITD mutated AML patients when used as a post-allogeneic HSCT maintenance. Importantly, clinical trials reported a low rate of toxicities requiring sorafenib discontinuation. The aim of our analysis was to evaluate the real-life experience in patients treated with post-allogeneic HSCT sorafenib maintenance therapy for FLT3-ITD AML with a particular focus on tolerability and toxicity-related treatment interruption. We conducted a single-center retrospective study on 30 FLT3-ITD AML patients undergoing allogeneic HSCT in complete remission between 2017 and 2020 and who received sorafenib maintenance. 26 patients (87%) experienced toxicities leading to dose reduction (n=9) or direct interruption (n=17). Average time on sorafenib was 125 days (range 1-765). Most common toxicities were skin, gastrointestinal, and hematologic. Among patients who had a dose reduction, 4 eventually interrupted the drug and 5 were able to continue. Among patients who interrupted sorafenib because of toxicities, 7 were re-challenged with good tolerance in 3 cases. Overall, 18 patients (60% of the entire cohort) definitively discontinued sorafenib because of toxicities. 14 patients were thereafter switched to midostaurin. Importantly, with a median follow-up of 12 months, the median overall survival was not reached suggesting a positive impact of sorafenib maintenance despite the high rates of treatment interruption. In conclusion, our real-life analysis reveals high rates of toxicity-related interruption of sorafenib maintenance after allogeneic HSCT. Interestingly, our results suggest the feasibility of re-challenging with sorafenib and/or of switching to other maintenance approaches in case of intolerance.